An exploration of food industry led reformulation on fortified food staples in Ireland. (22nd December 2020) - McMenemy, Daragh; Kelly, Frances; Sweeney, Mary Rose
Abstract: Background: Food industry led reformulation efforts have attempted to address the prevalence of obesity by modifying nutrient compositions in food products. This study explored progress in nutrient composition alterations in products in Irish supermarkets by comparing the nutrient labels of products sold in 2014 and 2017. Methods: We conducted two supermarket audits in 2014 and 2017 to examine the changes in the nutrient profile of cereals, breads, spreads, unflavoured milks, yogurts and juices. Information on the nutrients of interest to the study (energy, protein, fat, carbohydrate, saturated fat, salt, sugar and some micronutrients) were extracted and stored in Microsoft Excel. The nutrient profile of each product was compared across the two timepoints. Our study shows that the mean level of sugars in cereals remains high and that the mean level of salt remains high in cereals, breads, and spreads. Results: In total, 143 products were directly compared (86 cereals, 26 breads, 17 spreads and 14 milks). Our study shows that the composition of salt and sugar in cereal, bread, spreads and milk has declined by 12 and 7%, respectively. Saturated fat has declined in cereals (7%), but has increased in breads (12%), spreads (1%), and milks (5%). Manufacturers increased the serving sizes in nine cereals and one milk. Conclusions: From a population health perspective, the results are encouraging but care should be exercised by the food industry not to allow total fat and saturated fat levels to creep upwards. Further research and engagement of public health specialists and the food industry are needed.